Churchill's children. The evacuee experience in wartime Britain - Welshman, John (New York, 2010)
"Based on the stories of thirteen children and adults, Churchill's Children tells the often moving story of the evacuation of schoolchildren in Britain during the Second World War, from the first mass evacuations of 1939 through to the lesser-known but equally important evacuations of 1940 and 1944.